Variasi Dimensi Pencetak Pakan Ikan Lele Dengan Kapasitas 40 Kg/Jam - Pambudi, Mochamad Arya Rosydianto; Istiqlaliyah, Hesti (Jurnal Mesin Nusantara, 2022)
Indonesia is the second most biodiverse country after Brazil in Latin America. However, in the fisheries sector, Indonesia can be called the first richest country. There are approximately 2,000 species of fish found in Indonesian waters. Dumbo catfish (Clarias gariepinus) is one type of freshwater fish that is busy being cultivated by people in Indonesia, especially in the province of East Java, especially in Bangkok Village, Gurah District, Kediri Regency. Problems that often occur in fish farming are feed and complain about the high price of commercial feed so that freshwater fish cultivators can spend about 60-70% of the total cost required for cultivation. After reviewing the problems faced by catfish cultivators, the researchers have a solution for these problems, namely by designing a fish feed printing device with a screw press mechanism with a capacity of 40 kg/hour. In this design process, the method used is the design and development method. Based on the test results from the design of the fish pellet extruder machine with a capacity of 40 kg/hour, it can be concluded with a pellet molding machine with a variety of die (mold) with a diameter of 2 mm and 4 mm, the material is made of iron plate with a thickness of 1.8 mm. For driving the cutting blades using an electric motor with a power of 1.5 and a rotation of 1400 rpm with a rotation of 360º. The cutting knife uses stainless steel with a thickness of 0.8 mm. And the results of the machine test with a printed capacity is 39.83 kg/hour.